Urgensi Kreativitas Guru dalam Memanfaatkan Lingkungan Sekolah sebagai Sumber Belajar Siswa Kelas Awal di MI Amir Al-Jannah Tippulue - Mulkifah, Auliah; Sultan, Muslihin (Institut Agama Islam Negeri (IAIN) Bone, 2023)
This research aims to describe the creativity of teachers in utilizing the school environment as a learning resource in the early grades of MI Amir Al-Jannah Tippulue. This research is a qualitative research with a case study type involving six students and four teachers. Data collection is done through observation, interviews, and documentation. Data were obtained and analyzed using qualitative descriptive analysis with three stages: data reduction, describing data, and making conclusions. The results showed that the form of teacher creativity in utilizing the school environment as a learning resource for early grade students was seen from the teacher's ability to introduce the environment to students, introduce objects found in the school environment, and prepare learning resources that students could learn. There are also factors supporting and inhibiting teacher creativity in utilizing the school environment as a learning resource for early grade students seen from a conducive environment for students to learn, adequate school facilities so that students in learning can focus on something they are learning. Inhibiting factors such as the limited time experienced by the teacher during the learning process in the school environment and students who are less focused while studying in the school environment because they are busy playing. The importance of teacher creativity in utilizing the school environment because students see firsthand something they learn so that the learning process is more meaningful, interesting, and fosters student learning activities.